Printing and curing of conductive ink track on fabric using syringe deposition system with DLP projector and hot plate - Khirotdin, Rd. Khairilhijra; Mohamad Zainuri, Mohamad Izwan Saifudin; Ishak, Afiqah Izzati; Hassan, Nurhafizzah; Kamarudin, Khairu; Ibrahim, Mohd. Rasidi; Abdul Haq, Reazul Haq; Ibrahim, Mustafa; Sau’de, Nasuha; Mohd. Faizan Marwah, Omar (EDP Sciences, 2017)
Printing is a technique to transfer ink onto substrates to create pattern and syringe deposition system has shown some great potential in printing due to its ability to produce filamentary bead tracks which is important concerning conductivity and easily adopted on conformal surfaces which could not be realized by conventional technique. Fabrics with integrated electrical features able to create intelligent articles and may potentially open up new perspective areas of application in textile printing. However, the applicability of this technique on fabrics remains unknown which the ink used has to meet certain requirements including high electrical conductivity, resistance to oxidation, dry out without clogging, good adhesion with suitable viscosity and surface tension. Thus, there is a need to do this study which is to determine the feasibility of syringe deposition system to print a conductive ink tracks using silver epoxy-based conductive ink on fabric substrate via lycra material. This study is also aim to investigate the feasibility of using DLP projector with hot plate as another source of heat to be used in curing the ink tracks on fabric. The effect of printing and curing parameters to the characteristics and conductivity of the ink track is investigated. Several mechanical and electrical tests were also administered to determine the cure, hardness, adhesion and resistance level of the ink tracks. The results obtained were as expected which higher printing speed and lower deposition height used, a narrower and thinner ink tracks were produced. Sample with 4 mm/s of printing speed and deposition height of 1 mm resulted in dimension closer to the targeted dimension. The longer curing time and higher temperature used, a lower resistance is produced. The lowest resistance achieved is 0.9 Ω cured at 150°C for 60 minutes. The conductivity of the ink track was affected by curing process and cross-sectional area of the ink track. It is proven that a syringe deposition system is capable of printing the ink track and DLP projector with hot plate is suitable to cure the ink track properly on fabric.